2005
DOI: 10.1074/jbc.m504215200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Mlc, a Global Regulator of Sugar Metabolism in Escherichia coli

Abstract: Mlc from Escherichia coli is a transcriptional repressor controlling the expression of a number of genes encoding enzymes of the phosphotransferase system (PTS), including ptsG and manXYZ, the specific enzyme II for glucose and mannose PTS transporters. In addition, Mlc controls the transcription of malT, the gene of the global activator of the mal regulon. The inactivation of Mlc as a repressor is mediated by binding to an actively transporting PtsG (EIICB Glc ). Here we report the crystal structure of Mlc at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
69
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 44 publications
(54 reference statements)
2
69
0
1
Order By: Relevance
“…The dimerization appears to be related to the structural instability of the mutant protein. It has been shown that mutations of residues that coordinate a zinc ion in O-domain disturb the DNA-binding activity of Mlc (19). The D-domain of Mlc, which is responsible for DNA binding, is far away from O-domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dimerization appears to be related to the structural instability of the mutant protein. It has been shown that mutations of residues that coordinate a zinc ion in O-domain disturb the DNA-binding activity of Mlc (19). The D-domain of Mlc, which is responsible for DNA binding, is far away from O-domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A central sheet consisting of five strands is flanked by three ␣-helices and two short ␤-strands. Residues 195-380 form O-domain with a four-stranded sheet sandwiched asymmetrically by eight ␣-helices on one face and by one ␣-helix on the other face and contains a zinc ion known to play a structural role (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It further has an adjacent regulatory zinc-binding site, which is required for repressor activity (60) and is provided by the segment topologically equivalent to the protruding ␤-ribbon ␤13␤14 in MecR2. In contrast to the latter, however, this segment is folded back toward the body of the molecule in Mlc, in a fashion similar to that in ROK glucokinase from E. coli (70) and glucomannokinase from Arthrobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no structural data on XylR available. E. coli protein Mlc is the only functionally and structurally characterized ROK family protein with DNA repressor function (60,67). Mlc is a dimeric/tetrameric transcriptional repressor that controls the utilization of glucose in E. coli (68).…”
Section: Resultsmentioning
confidence: 99%